Analysis of scarlett product purchase decisions to consumers in Cikarang through product quality, prices and promotions - Agustini Tanjung; Nur' Aeni (Institute of Computer Science (IOCS), 2022)
This study aims to find out how the influence of product quality, price and promotion on purchasing decisions for scarlett products in Cikarang. This study uses quantitative analysis methods, namely research using numbers and statistical analysis. The method used in this study uses partial regression analysis (Partial Least Square/PLS) assisted by SmartPLS 3.0 software. Based on the results of research that has been carried out that product quality has a positive and significant effect on purchasing decisions. This is supported by the results of hypothesis testing T-Statistics 1.967 than T-table which is 4.466 with an effect of 0.275 and P-value > 0.05 of 0.000. Price has a positive and significant effect on purchasing decisions, this is supported by the results of hypothesis testing T-Statistics > than T-table which is 2.480 or 1.967 with an effect of 0.275 and P-value > 0.05 of 0.219. promotion has a positive and significant effect on purchasing decisions. This is supported by the results of hypothesis testing TStatistics > than T-table, which is 5.711 (1.967) with an effect of 0.077 and P-value > 0.05 of 0.000.